2021
DOI: 10.1097/eja.0000000000001539
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and airway complications of Parker Flex-Tip tubes and standard endotracheal tubes during airway manipulation

Abstract: BACKGROUND Despite reported superior intubation outcomes associated with Parker Flex-Tip (PFT) tubes compared with those associated with standard polyvinylchloride tubes, the efficacy and safety of PFT tubes remain uncertain. OBJECTIVES To compare the intubation outcomes between PFT and conventional standard polyvinylchloride tubes. DESIGN Meta-analysis of randomised controlled trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…Most authors estimate loss of radial length as the most important radiologic parameter influencing the functional outcome, and it seems that any technique maintaining the radial length may attain better functional results. However, loss of radial length has been reported in various forms in the literature [13]. Many studies have shown that the number or position of K-wires does not influence radial inclination.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors estimate loss of radial length as the most important radiologic parameter influencing the functional outcome, and it seems that any technique maintaining the radial length may attain better functional results. However, loss of radial length has been reported in various forms in the literature [13]. Many studies have shown that the number or position of K-wires does not influence radial inclination.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the strength of the results and to guard against statistical errors of type I and type II, we performed trial sequential analysis (TSA) as previously described ( 25 , 26 ). We calculated the diversity-adjusted information size using 80% power while maintaining an overall two-sided type I error of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…To minimize false-positive results attributed to multiple testing and sparse data, trial sequential analysis (TSA) with TSA viewer version 0.9.5.10 Beta ( www.ctu.dk/tsa ) was conducted to test the robustness of the cumulative evidence as previously reported ( 24 ). Following the calculation of the required information size (RIS) and the trial sequential monitoring boundaries, the correlation between the cumulative Z curve and the TSA boundary was examined.…”
Section: Methodsmentioning
confidence: 99%